PERSONALIZATION IN DIGITAL MARKETING: EXPLORING ITS IMPACT ON CONSUMER TRUST AND LOYALTY - Wuryantini, Aris (Management Studies and Business Journal (PRODUCTIVITY), 2025)
In the ever-evolving digital era, personalization in digital marketing has become an important strategy for companies to increase customer engagement and loyalty. This research aims to explore the factors that mediate the relationship between digital marketing personalization and consumer loyalty. Through a Systematic Literature Review (SLR) approach with PRISMA methodology, this research identifies five main factors that act as mediators: perceived trust and transparency, customer involvement and emotional connection, perceived value and relevance, privacy and data security concerns, and brand relationships and commitment. The findings show that transparency in data use and relevant personalized experiences can increase customer trust, which in turn strengthens loyalty. This research provides valuable insights for marketing practitioners in designing ethical and effective personalization strategies, and highlights the importance of maintaining data privacy and security in building long-term relationships with customers.